Thoracic spine pain - Aleksey Ivanovich Isaikin; A V Kavelina (Неврология, нейропсихиатрия, психосоматика, 2013)
Thoracic spine pain, or thoracalgia, is one of the common reasons for seeking for medical advice. The epidemiology and semiotics of pain in the thoracic spine unlike in those in the cervical and lumbar spine have not been inadequately studied. The causes of thoracic spine pain are varied: diseases of the cardiovascular, gastrointestinal, pulmonary, and renal systems, injuries to the musculoskeletal structures of the cervical and thoracic portions, which require a thorough differential diagnosis. Facet, costotransverse, and costovertebral joint injuries and myofascial syndrome are the most common causes of musculoskeletal (nonspecific) pain in the thoracic spine. True radicular pain is rarely encountered. Traditionally, treatment for thoracalgia includes a combination of non-drug and drug therapies. The cyclooxygenase 2 inhibitor meloxicam (movalis) may be the drug of choice in the treatment of musculoskeletal pain.